Exploring the Relationship between Digital Literacy Skills and Student Success in Online Science Courses in Indonesia - Sari, Anita (International Journal of Online and Distance Learning, 2024)
Purpose: The aim of the study was to investigate the exploring the relationship between digital literacy skills and student success in online science courses in Indonesia. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Recent research on digital literacy skills and student success in online science courses in Indonesia indicates a strong link between proficient digital skills and academic achievement. Students who demonstrate competence in areas like information literacy and online collaboration tend to perform better and show higher levels of engagement in their courses. This highlights the significant impact of digital literacy on enhancing learning outcomes and fostering self-directed learning among Indonesian students in online science education. Unique Contribution to Theory, Practice and Policy: Theoretical framework, technology acceptance model (tam) & community of inquiry framework may be used to anchor future studies on the exploring the relationship between digital literacy skills and student success in online science courses in Indonesia. Institutions should integrate digital literacy training into science curricula from early educational stages to higher education. Advocate for the development and adoption of national or institutional standards for digital literacy in education.